Shared neural correlates for building phrases in signed and spoken language - Blanco-Elorrieta, Esti (Sci Rep, 2018)
Research on the mental representation of human language has convincingly shown that sign languages are structured similarly to spoken languages. However, whether the same neurobiology underlies the online construction of complex linguistic structures in sign and speech remains unknown. To investigate this question with maximally controlled stimuli, we studied the production of minimal two-word phrases in sign and speech. Signers and speakers viewed the same pictures during magnetoencephalography recording and named them with semantically identical expressions. For both signers and speakers, phrase building engaged left anterior temporal and ventromedial cortices with similar timing, despite different linguistic articulators. Thus the neurobiological similarity of sign and speech goes beyond gross measures such as lateralization: the same fronto-temporal network achieves the planning of structured linguistic expressions.